Duration of Antiresorptive Effects of Low‐Dose Zoledronate in Osteopenic Postmenopausal Women: A Randomized, Placebo‐Controlled Trial. (January 2014) - Grey, Andrew; Bolland, Mark; Mihov, Bobby; Wong, Sumwai; Horne, Anne; Gamble, Greg; Reid, Ian R
ABSTRACT Annual intravenous administration of 5 mg zoledronate decreases fracture risk, but the optimal dosing regimen for zoledronate has not been determined. We set out to evaluate the antiresorptive effects of a single administration of lower doses of zoledronate. A total of 180 postmenopausal women with osteopenia enrolled in a double‐blind, randomized, placebo‐controlled trial over 2 years at an academic research center. Participants were randomized to a single baseline administration of intravenous zoledronate in doses of 1 mg, 2.5 mg, or 5 mg, or placebo. The primary endpoint was change in bone mineral density(BMD) at the lumbar spine. Secondary endpoints were change in BMD at the proximal femur and total body, and changes in biochemical markers of bone turnover. After 2 years, the change in spine BMD was greater in each of the zoledronate groups than in the placebo group; values are mean (95% confidence interval [CI]) difference versus placebo: zoledronate 1 mg 4.4% [2.7% to 6.1%]; 2.5 mg 5.5% [3.9% to 7.2%]; 5 mg 5.3% [3.8% to 6.7%], p < 0.001 for each dose). Change in BMD at the total hip was greater in each of the zoledronate groups than the placebo group (mean [95% CI] difference versus placebo: zoledronate 1 mg 2.6% [1.5% to 3.7%]; 2.5 mg 4.4% [3.5% to 5.3%]; 5 mg 4.7% [3.7% to 5.7%], p < 0.001 for each dose). Each of the bone turnover markers, β‐C‐terminal telopeptide of type I collagen (β‐CTX) and procollagen type‐I N‐terminal propeptide (P1NP), was lower in each of the 2.5‐mg and 5‐mg zoledronate groups than the placebo group throughout the trial (p < 0.001 versus placebo for each marker for each dose at each time point). For each endpoint, changes were similar in the 2.5‐mg and 5‐mg zoledronate groups, whereas those in the 1‐mg group were smaller than those in the other zoledronate groups. These data demonstrate that single administrations of zoledronate 1 mg or 2.5 mg produce antiresorptive effects that persist for at least 2 years. Trials assessing the antifracture efficacy of intermittent low doses of zoledronate, in particular the 2.5‐mg dose, are justified. © 2014 American Society for Bone and Mineral Research.